Henry Foe's dilemma. Issue 2 (June 2022) - Ward, Ian
Abstract: In 1722, Daniel Defoe published A Journal of the Plague Year – a supposed account of the 'great plague' of 1665. It is commonly thought to be one of his most incisive pieces of 'realist' fiction. And, in our moment, one of his most prescient. The purpose of this paper is to revisit Defoe's Journal in order to stimulate reflection on our present experience of living through the 'plague year' of 2020. There is much, as we shall see, about governance during a plague that is resonant – but much also about 'hearts melted into tears', about suffering, how it is felt and how it is perceived. The purpose of the Journal, according to Defoe at least, was to inform 'those who come after', so that they might be better prepared, so that they would not make the same mistakes. We will see.